(untitled) (Research, Society and Development, 2022)
Introduction: Clinical supervision in nursing training is essential for the professional development of the student, the complexity of supervision brings a breadth of knowledge, concepts and practices that characterize the relationship between student and supervisor as complex. Objective: This study aims to analyze the perceptions and insights of supervisory nurses specialized in the context of family health nursing, about supervision in clinical education taking into account their experiences Significant. Methodology: Qualitative field research, an exploratory-descriptive study was developed, with the objective of exploring and describing the phenomenon of clinical supervision in Nursing. For this purpose, interviews were conducted with 10 supervising nurses specialized in family health. Results: The main objective of clinical supervision is the guidance and follow-up of nursing students, providing contact with real clinical nursing practice. Conclusions: It is concluded, of the great importance of the implementation of clinical supervision for an effective professional development, so that better nurses are trained, thus improving the quality of health services, a better organization of cl units clinics and an increase in nurses’ satisfaction.